Analisis Efektifitas Penggunaan Metode Kooperatif Tipe Learning Together pada Pembelajaran PAI di SMP Al Mahrusiyah Ngampel Kediri - Rinto Arahap; Makhromi Makhromi (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2020)
This research is on the big topic of learning technology. The researcher tries to reveal the cooperative method of learning together type which is implemented in Al Mahrusiyah Junior High School in Kediri on the subject of Islamic Religious Education. The cooperative method of learning together type is used as a solution so that the class can be effective so that the objectives of learning can be achieved. The objectives of this study are (1) To reveal the effectiveness of the cooperative method of learning together type in SMK Al Mahrusiyah. (2) To reveal the impact of the cooperative method of learning together type in SMK Al Mahrusiyah. This research is a descriptive qualitative study using verbal data and analyzed by the source triangulation method. The results of the research are (1) The cooperative method of learning together type is felt to be implemented effectively with evidence of an increase in the value above the KKM value, (2) The impact arising from the application of the cooperative method of learning together is that students are more active.